PENGARUH KOMPETENSI APARAT DESA DAN IMPLEMENTASI SISKEUDES DI ERA DIGITAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN TELLU LIMPOE KABUPATEN BONE - Satriyanah, Dewi; Basir MR, Basri; Fuada, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of village apparatus competence and the implementation of SISKEUDES (Village Financial Management Information System) in the digital era on the accountability of village fund management in Tellu Limpoe District, Bone Regency. The increasing allocation of village funds, reaching Rp10.22 billion in Tellu Limpoe in 2024, demands strong accountability mechanisms supported by competent human resources and reliable information systems. This study employs a quantitative causal-associative approach with a survey method and explanatory research design. Primary data were collected through questionnaires distributed to 77 village apparatus members and BPD members across 11 villages. The research instrument used a Likert scale and data were analyzed using multiple linear regression with SPSS version 25. The results show that village apparatus competence has a positive and significant effect on the accountability of village fund management (t = 5.353; sig. = 0.000). The implementation of SISKEUDES has a positive but not significant effect (t = 1.574; sig. = 0.120). Simultaneously, both variables significantly influence accountability (F = 27.432; sig. = 0.000), explaining 42.6% of the variance. These findings indicate that improving village apparatus competence is a critical factor in enhancing accountability in the digital era, while SISKEUDES implementation still requires optimization of technological infrastructure to deliver its full potential impact.